2017
DOI: 10.1016/j.cej.2016.11.123
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fouling development under dynamic membrane filtration operation

Abstract: This research is a contribution towards evaluating the appropriate fouling mechanism responsible for the flux decline under dynamic membrane (DM) filtration and its formation mechanism by using gravity-driven filtration in a specifically designed experimental setup. Series of extended short term filtration experiments were performed at varying operating conditions of mixed liquor suspended solids (MLSS) concentrations, trans-membrane pressures (TMP) and mesh pore sizes. Blocking models were applied to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The result obtained over the first 30 days of operation confirms a previous study (Saleem et al, 2017) which demonstrated that the mesh pore size does not significantly affect the filtration flux (Fig. 2).…”
Section: Dynamic Membrane Behavioursupporting
confidence: 90%
See 1 more Smart Citation
“…The result obtained over the first 30 days of operation confirms a previous study (Saleem et al, 2017) which demonstrated that the mesh pore size does not significantly affect the filtration flux (Fig. 2).…”
Section: Dynamic Membrane Behavioursupporting
confidence: 90%
“…Short-term filtration experiment is a simple way to evaluate the performance of the coarse meshes used to develop DM (Li et al, 2012). These experiments were performed in a separate filtration system according to the procedure previously described in Saleem et al (2017).…”
Section: Short-term Filtration Experimentsmentioning
confidence: 99%
“…Intermediate blocking is similar to the complete blocking model, but particles are able to deposit on other particles. Saleem et al [56] concluded that cake filtration could adequately describe fouling mechanisms in sludge formed DM filtration under constant pressure.…”
Section: Dynamic Membrane Formation Mechanismmentioning
confidence: 99%
“…However, thicker layers and dense fouling cause a loss of membrane performance. The parameters that must be taken into consideration to limit the formation of fouling are the same that are involved in the DM formation [57].…”
Section: Literature Analysis On the Microplastic And Its Removal Bmentioning
confidence: 99%